Fracture resistance of polyetheretherketone, Ni-Cr, and fiberglass postcore systems: An in vitro study - Hossein Pourkhalili; Donya Maleki (Wolters Kluwer Medknow Publications, 2022)
Background: It is unclear which the material is a better choice for post and core rehabilitation systems in endodontically treated teeth. This study aimed to compare the fracture resistance of three different postcore systems. Materials and Methods: In this in vitro study, 33 extracted premolars were treated endodontically and divided into three groups, namely (A) the prefabricated fiberglass postcomposite core, (B) the Ni-Cr cast postcore, and (C) the polyetheretherketone (PEEK) postcore groups. After postcementation, the core was restored with Ni-Cr crown. By a universal testing machine, the fracture resistance of the posts was assessed. Furthermore, types of fractures were determined with radiography and confirmed objectively by cutting the acryl resin boxes. The data of the fracture resistance were analyzed using the one-way ANOVA and Tukey test, and the data of the fracture pattern were analyzed using Fisher's exact test (P < 0.05). Results: The fracture resistance was significantly higher in Group B (Ni-Cr) than in Group C (PEEK) (P = 0.001) and Group A (fiberglass) (P < 0.001). Moreover, the fracture resistance was higher in Group C (PEEK) than in Group A (fiberglass) but was not statistically significant (P = 0.405). The fracture pattern was different in all the groups based on the types of fracture (P = 0.009) and the repairability of fracture (P = 0.036). Conclusion: The present study showed that the fracture resistance was significantly higher in the Ni-Cr post than in the fiberglass and PEEK posts. Further, the fracture mode was more repairable in teeth restored with the PEEK post, as compared to the other posts.